Short-Term Effects of Square Stepping Exercise on Cognitive and Social Functions in Sedentary Older Adults: A Home-Based Online Trial (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2022)
Background: The Square Stepping Exercise (SSE) is an exercise training program integrating physical exercise and cognitive components. The potential of SSE in deferring cognitive decline in older adults is encouraging. However, the coronavirus pandemic has made it harder for older adults worldwide to exercise together in person. Therefore, the present study aimed to investigate the short-term effects of a home-based online SSE trial on cognitive and social functions in sedentary older adults. Methods: A sample of 24 older adults (2 men, 22 women) took part in the current study. Seven participants (2 men, 5 women) completed home-based online SSE sessions under tighter safety regulations, whereas other 17 women attended SSE sessions in person when group exercise with more than 5 people were permitted. To investigate the effects of the online SSE on cognitive and social functions compared to the in-person SSE, 2 times (pre vs. post) × 2 groups (online vs. in-person) mixed ANOVAs were conducted with classic and robust statistical methods on the scores of the Trail Making Test (TMT), the subscale scores of the Physical Activity Group Environment Questionnaire, and the score of the Subjective Vitality Scale. Results: The interaction between time and groups was significant on the TMT-B to TMT-A (B/A) ratio score (p = .049) and the subscale scores of Individuals Attractions to the Group‒Task (p = .034) and ‒Social (p = .037). The B/A ratio score is an indicator of executive control function. The online SSE group’s ratio score slightly decreased over the sessions, whereas the ratio score significantly increased in the in-person group. As for group cohesion, participants’ involvements with the group task and social interaction with their group were enhanced in the online SSE group over the sessions, compared to the in-person SSE group. Conclusions: In this study, SSE was carried out online for a short-term and found to be successful to enhance executive function and group cohesion in sedentary older adults. Considering the coronavirus pandemic circumstances, it is valuable to examine the long-term effects of the online SSE in older adults in future research.